2011
DOI: 10.3347/kjp.2011.49.4.441
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Egg Positive Rates ofEnterobius vermicularisamong Preschool Children in Three Korean Localities

Abstract: This survey was performed to investigate and compare egg positive rates (EPRs) of Enterobius vermicularis among preschool children in 3 Korean localities (Chuncheon-si, Inje-gun, and Paju-si) in 2008. A total of 7,048 preschool children were examined. Overall, the total EPR was 4.0%; the EPR was the highest in Chuncheon-si (5.6%), followed by Inje-gun (4.5%) and Paju-si (3.4%). The EPR of boys (4.9%) was higher than that of girls (3.1%). The EPR significantly increased with age, with the highest observed in 5~… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 11 publications
1
5
0
Order By: Relevance
“…Five to 6-year-old children might have more frequent contact in kindergartens than children 2–4 years of age. The egg positive rate for E. vermicularis was also found to significantly increase with age, as previously reported [ 6 , 7 ]. With regard to gender, no significant statistical difference was observed between boys and girls, which was consistent with other reports [ 12 , 15 , 18 ].…”
Section: Discussionsupporting
confidence: 87%
“…Five to 6-year-old children might have more frequent contact in kindergartens than children 2–4 years of age. The egg positive rate for E. vermicularis was also found to significantly increase with age, as previously reported [ 6 , 7 ]. With regard to gender, no significant statistical difference was observed between boys and girls, which was consistent with other reports [ 12 , 15 , 18 ].…”
Section: Discussionsupporting
confidence: 87%
“…E. vermicularis infection occurs by ingesting the eggs of infectious stage through contact with contaminated objects or air transmission [ 1 , 3 ]. Enterobiasis is generally asymptomatic but can cause anal pruritus, discomfort, insomnia, or anxiety especially in young children [ 4 ]. Although it is not considered a serious illness, it can sometimes cause serious morbidity such as appendicitis and perianal dermatitis [ 2 ].…”
mentioning
confidence: 99%
“…In the Republic of Korea (= Korea), surveys of E. vermicularis infection have been continuously conducted, and it has been shown that its prevalence is decreasing gradually over time [1][2][3][4][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26]. However, most of the previous surveys were conducted under limited conditions, i.e., in local regions and targeting specific group during a short period of time [1][2][3][4][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26].…”
mentioning
confidence: 99%
See 2 more Smart Citations